The Reflection of Organizational Citizenship Behavior on Knowledge Sharing : An Applied Research in The Baghdad Al-Karkh Health Department - Alaa Alshamaa, Hussain; Ali AL-Ameri, Sarah (Journal of Economics and Administrative Sciences, 2024)
The objective of the study is to assess the degree of knowledge sharing and diagnose organizational citizenship behavior and explain the existence of a correlation between organizational citizenship behavior with its dimensions(altruism, consciousness of conscience, politeness, voluntary participation, and sports spirit) and knowledge sharing with its dimensions (enjoyment in helping others ,competent self-knowledge, senior management support, organizational incentives, and information as well as communication technology). Targeting 846 employees who work at the department’s headquarters. The study has been carried out in Al-Karkh Health Department. With the use of a specific method for random sample selection, the 264 research participants were divided across the divisions and areas of the department. The assumes that organizational citizenship behavior and information sharing inside the Al-Karkh Health Department are correlated and have an impact on each other. The research sample was given a questionnaire to fill out to collect data to collect data. With the use of programs AMOS and SPSS, several statistical techniques have been applied to anaylse data including arithmetic mean, standard deviation, and the coefficient of variation. The study’s key finding most important results that there is an influence between the factors under investigation. Paper: Research paper.